Proof Power of Authentic Deed Transfer of Land Rights in Legal Perspective of Civil Procedures - Yuda Anrova; Eman Suparman; Hazar Kusmayanti (Universitas Ahmad Dahlan, 2021)
Introduction to The Problem: Evidence is a process carried out by the parties in resolving disputes to prove the arguments presented before the judge who decides the legal dispute so that the judge can decide as fairly as possible. Evidence under the civil procedure law is regulated in Article 164 HIR. Supreme Court decision number 3591K/Pdt/2018 discusses documentary evidence in the form of an agreement to transfer and transfer land rights and states that the deed has no legal force.Purpose/Objective Study: The purpose of the study was to determine the legal considerations for the strength of authentic deed evidence in the Supreme Court Decision number 3591K/Pdt/2018, connected with civil procedural law. The research method used is a normative juridical approach to the research specification in descriptive-analytical analysis and qualitative normative.Design/Methodology/Approach: The method used in this research is normative juridical research which focuses on the applicable legal provisions.Findings: The research results that the authentic deed submitted by the Defendants in the Reconvention as evidence has external and formal evidentiary power. However, authentic deeds that are perfect and binding do not have a coercive or decisive character. Authentic deed evidence can be invalidated if there is evidence of the opponent which can prove otherwise. Based on the decision of the Supreme Court number 3591K/Pdt/2018, the Notarial Deed of the Transfer of Land Rights Agreement has no legal force because land rights have been transferred and building use rights are attached.Paper Type: Research Article